Cermets's utilization and his effect in the machined surface multifactorial analyzed - Sarache, Luis (Revista Técnica da Faculdade de Engenharia da de Zulia, 1970)
The finished superficial one is stuudied and analyzes in national steels of the mechanized on by tools of hard metal (cermets) (TNMG); when they actuate the variables: depth, advance and speed of cut, type of tool and material of the piece, using the experimental design, applying a Fractional Factorial Design (DFF) 2 7-4, which diminishes significantly the effort, time and cost of the experimentation on having realized the anaIysis multifactorial. Since result takes the advance as an only one factor of an individual way, this one will not be anaIyzed by his little effect in the significant one on the finished one, since the analysis is in use following the methodology for the case of graphs of two routes with interaction or combination of variables as: depth to 0.5 mm. And speed of cut to 266.41 m/min, they turn out to be the most favorable situation on having achieved a value I mediate of 3.51 Âµm; whereas the least favorable, is achieved by the same speed but to major depth 1.5 mm. There is verified experimentally that on having increased the depth of cut it worsens the finished one, this situation, very similar lo the one that happens with the wear of the flank of tool, nevertheless. the fact of not obtaining the operational total factor to improve the finished one they do not concern since what is claimed is to determine the trends for the search of the optimization.